Creation, sin, covenant, and salvation : a primer for Biblical theology - Meadors, Edward P., 1964- (Eugene, OR : Cascade Books, 2011)
This is a short accessible synopsis of the Christian worldview for readers of all ages. Sprinkled with anecdotes, the book eases readers into a succinct yet comprehensive discussion of biblical thought. The final chapter explains the authority, practical value, and intended purpose of Scripture. Meadors inspires readers to think critically about the real life believability of the Christian faith, especially its intellectual coherence. In keeping with biblical theology, the book affirms the continuity of biblical revelation from beginning to end before consummating in the resurrection of the dead and God's restoration of all creation.
Eden : fact or fairy tale? -- It's a humpty dumpty world : sin and its consequences -- The covenant solution : it's all about relationships -- Salvation : what God made, he can fix -- The self-authenticating power of Scripture.
Includes bibliographical references (p. 125-126).
Keywords: Bible -- Theology; Bible -- Evidences, authority, etc..; Covenant theology; Creation -- Biblical teaching; Sin -- Biblical teaching; Atonement